Composition for improving well cementation quality of oil and gas well and application thereof

By adding nano-oxides, inorganic whiskers, carboxy-containing low-molecular polymers and hydroxy-containing polymers to the oil well cement, the problem of oil well cement stones being easily broken under complex working conditions is solved, and the problem of oil well cement stones being easily broken under complex working conditions is significantly improved. Its compressive strength, flexural strength and water loss reduce, meeting the cementing needs of complex oil and gas wells.

CN119490319APending Publication Date: 2025-02-21SINOPEC OILFIELD SERVICE CORPORATION +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311052690.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-21
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The cement stone of the oil well is prone to breaking under complex working conditions, with low tensile strength, poor fracture resistance and low impact toughness, making it difficult to meet the requirements of complex oil and gas reservoirs and special working conditions.

Method used

A composition, including nanooxides, inorganic whiskers, carboxyl-containing low-molecular polymers, hydroxyl-containing polymers and solvents, is used as a reinforcement for oil well cement, and improves cement stones by adjusting pH value and mixing process. Compressive strength, flexural strength and reduce water loss.

Benefits of technology

It significantly improves the compressive strength and flexural strength of cement stone in Class G oil wells, reduces water loss, enhances the comprehensive mechanical properties of cement stone, and is suitable for cementing applications of complex oil and gas wells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490319A_ABST
    Figure CN119490319A_ABST
Patent Text Reader

Abstract

The invention provides a composition for improving the well cementation quality of an oil and gas well and application of the composition. The composition provided by the invention comprises a nano oxide, an inorganic whisker, a carboxyl-containing low-molecular polymer, a hydroxyl-containing high-molecular polymer and a solvent, and is added into oily cement as a reinforcing agent, and when the addition amount of the composition is 4-6wt% of the mass of G-grade oil well cement, the compressive strength of G-grade oil well cement stone can be improved by more than 50%, the breaking strength can be improved by more than 50%, and the oil well cement stone can be effectively prevented from being damaged. The oil well cement drag reducer has good compatibility with existing oil well cement drag reducers and fluid loss agents, and is beneficial to field application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of oil and gas exploitation, and in particular relates to a composition for improving the cementing quality of oil and gas wells and an application thereof. Background Art

[0002] Wellbore sealing integrity is crucial to the production and development process of oil and gas fields, but as oil and gas exploration and development targets become more and more complex, the integrity of the cement ring faces severe challenges. Especially in complex deep natural gas wells, unconventional oil and gas horizontal wells and gas storage wells, the cement ring is subjected to very complex forces, usually facing high hydraulic stress and thermal stress, and has to withstand up to dozens of high-load repeated impacts. However, oil well cement is a brittle material with inherent defects such as low tensile strength, poor crack resistance and low impact toughness. Therefore, the integrity of the cement ring is very easy to be destroyed, resulting in the failure of the sealing integrity of the wellbore, which seriously affects the normal production, safety and benefits of oil and gas resources.

[0003] In recent years, my country has strengthened the construction of gas storage facilities. In 2019, my country's apparent natural gas consumption reached 306.7 billion cubic meters. In order to enhance the peak-shaving capacity of natural gas and solve the problem of "gas shortage" in some areas in winter, 27 gas storage facilities have been built across the country, but the peak-shaving capacity is only 12 billion cubic meters. During the operation of gas storage wells, under the "large in and large out" cycle injection and production work system, the cement sheath is easily damaged due to the drastic changes in stress it is subjected to, resulting in annular pressure problems.

[0004] In order to solve the problem of cement sheath being easily broken under complex working conditions and to improve the elasticity and strength of cement paste, domestic and foreign researchers have conducted in-depth research. Many experts and scholars at home and abroad have proposed and applied elastic-tough cement paste and self-healing cement paste technology. Elastic-tough cement paste can improve the brittleness of oil well cement paste and improve its impact resistance. However, this method has limited ability to reduce the brittleness of oil well cement paste, and on the other hand, it is based on the sacrifice of mechanical properties such as compressive strength of cement paste. The comprehensive fracture resistance of oil well cement paste still cannot meet the increasingly complex environment and development requirements; the number of repeated healing times and ability of expandable smart materials in self-healing cement paste are limited, and its long-term effectiveness has not yet been solved.

[0005] Traditional oil well cement is naturally brittle and has inherent defects such as low tensile strength, poor fracture resistance and low impact toughness. The existing elastic-toughness cement and self-healing cement technologies are still difficult to meet the requirements for cement integrity and long-term performance under complex oil and gas reservoirs and special working conditions. The problems of cement ring seal failure and annulus pressure are prominent. It is urgent to develop a material that can reduce the brittleness of cement and improve the mechanical properties of cement. Summary of the invention

[0006] One of the present inventions provides a composition, which includes nano oxide, inorganic whisker, carboxyl-containing low molecular polymer, hydroxyl-containing high molecular polymer and solvent.

[0007] In a specific embodiment, the composition includes 20 to 30 parts by mass of the nano oxide, 13 to 21 parts by mass of the inorganic whiskers, 5 to 11 parts by mass of the carboxyl-containing low molecular polymer, 0.82 to 1.05 parts by mass of the hydroxyl-containing high molecular polymer and 100 parts by mass of the solvent;

[0008] Preferably, the composition comprises 20 to 30 parts by mass of the nano oxide, 13 to 15 parts by mass of the inorganic whiskers, 5 to 11 parts by mass of the carboxyl-containing low molecular polymer, 0.82 to 1.05 parts by mass of the hydroxyl-containing high molecular polymer and 100 parts by mass of the solvent.

[0009] In a specific embodiment, the solid content of the composition is 30wt% to 58wt%; and / or

[0010] The pH of the composition is 7 to 7.8;

[0011] Preferably, the solid content of the composition is 31 wt % to 36 wt %.

[0012] In a specific embodiment, the nano-oxide is nano-silicon dioxide and / or nano-titanium dioxide; and / or

[0013] The inorganic whiskers are magnesium carbonate whiskers; and / or

[0014] The solvent is water.

[0015] In a specific embodiment, the carboxyl-containing low molecular weight polymer is polycarboxylic acid and / or polycarboxylate;

[0016] Preferably, the carboxyl-containing low molecular weight polymer is polyacrylic acid and / or sodium polyacrylate.

[0017] In a specific embodiment, the hydroxyl-containing high molecular polymer is at least one of polyvinyl alcohol, polyvinyl pyrrolidone, carboxymethyl cellulose, carboxymethyl chitosan and hydroxypropyl chitosan.

[0018] In a specific embodiment, the particle size of the nano-oxide is 3nm to 35nm; and / or the median particle size is 5nm to 15nm; and / or

[0019] The inorganic whisker has a length of 12 μm to 18 μm; and / or a diameter of 4 μm to 7 μm; and / or

[0020] The weight average molecular weight of the carboxyl-containing low molecular polymer is 1500 to 3000; and / or

[0021] The weight average molecular weight of the hydroxyl-containing high molecular polymer is 330,000 to 1.2 million;

[0022] Preferably, the particle size of the nano-oxide is 5 nm to 23 nm; and / or the median particle size is 6 nm to 10 nm;

[0023] and / or

[0024] The weight average molecular weight of the carboxyl-containing low molecular polymer is 2000 to 3000.

[0025] The second aspect of the present invention provides a method for preparing the composition according to the first aspect of the present invention, which comprises the following steps:

[0026] 1) mixing the solvent, the carboxyl-containing low molecular polymer and the nano oxide to obtain a dispersion;

[0027] 2) mixing the inorganic whisker, the hydroxyl-containing high molecular polymer and the dispersion, and adjusting the pH to obtain the composition.

[0028] In a specific embodiment, in step 1), the solvent, the carboxyl-containing low molecular polymer and the nano-oxide are mixed under ultrasonic treatment at 60° C. to 75° C. for 3 min to 7 min.

[0029] In a specific embodiment, in step 2), the temperature of mixing the inorganic whiskers, the hydroxyl-containing high molecular polymer and the dispersion is 60° C. to 75° C.; and / or the pH is adjusted to 7 to 7.8;

[0030] Preferably, the pH is adjusted with a mixture of magnesium sulfate and potassium carbonate;

[0031] Preferably, the molar ratio of magnesium sulfate to potassium carbonate is 1:1.

[0032] In the present invention, magnesium sulfate and potassium carbonate added to adjust the pH value form a magnesium carbonate precipitate suspended in the composition.

[0033] In a specific embodiment, the inorganic whisker is prepared by the following method:

[0034] a. mixing water and magnesium sulfate to obtain a magnesium sulfate solution;

[0035] b. mixing the magnesium sulfate solution and potassium carbonate, reacting to obtain the inorganic whiskers.

[0036] In a specific embodiment, based on the mass of water in step a, the amount of magnesium sulfate used is 13wt% to 20wt%, and the amount of potassium carbonate used is 15wt% to 27.5wt%.

[0037] In a specific embodiment, in step a, mixing is performed by stirring at 60° C. to 75° C.;

[0038] Preferably, the stirring speed is 200 r / min to 300 r / min.

[0039] In a specific embodiment, in step b, the reaction product obtained by the reaction is filtered, the filter residue is collected, and dried to obtain the inorganic whiskers;

[0040] Preferably, in step b, an aqueous potassium carbonate solution is added dropwise to the magnesium sulfate solution; and / or

[0041] The concentration of potassium carbonate in the potassium carbonate aqueous solution is 50 wt %; and / or

[0042] Based on the mass of water in step a, the amount of the potassium carbonate aqueous solution is 30wt% to 55wt%;

[0043] Preferably, the duration of the dripping is 50 min to 70 min; and / or

[0044] The drying temperature is 40°C to 50°C.

[0045] In a specific embodiment, in step b, the reaction conditions are stirring at 60° C. to 75° C. at a speed of 100 r / min to 150 r / min for 5 h to 8 h.

[0046] Application of the composition of the first invention or the composition prepared by the method of the second invention in oil and gas production, especially as an oil well cement enhancer;

[0047] Preferably, the oil well cement is at least one of Class A oil well cement, Class C oil well cement and Class G oil well cement. Beneficial effects of the present invention:

[0048] In view of the inherent defects of oil well cement stone such as low tensile strength, poor fracture resistance and low impact toughness, and the problem that the elastic and tough cement stone and self-healing cement stone in the prior art are difficult to meet the requirements of cement stone integrity and long-term performance under complex oil and gas reservoirs and special working conditions, the present invention provides a composition for improving the cementing quality of oil and gas wells and its application. The composition provided by the present invention comprises nano oxides, inorganic whiskers, carboxyl-containing low molecular polymers, hydroxyl-containing high molecular polymers and solvents. Among them, there is a synergistic effect between the nano oxides, inorganic whiskers, carboxyl-containing low molecular polymers and hydroxyl-containing high molecular polymers in enhancing the compressive strength and flexural strength of cement stone and reducing the water loss of cement stone. When the nano oxides, inorganic whiskers, carboxyl-containing low molecular polymers and hydroxyl-containing high molecular polymers are added to G-grade oil well cement as a reinforcing agent, and the addition amount is 4wt% to 6wt% of the mass of G-grade oil well cement, the compressive strength of G-grade oil well cement stone can be increased by more than 50%, the flexural strength can be increased by more than 50%, and the water loss can be reduced by 25.6%. At the same time, the nano oxides have good compatibility with the existing oil well cement drag reducers and water loss reducers, which is conducive to field application. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 The graphs are the viscosity change curves of the cement slurry of the blank group and the experimental group in the experiment of the effect of the composition on the thickening performance of oil well cement;

[0050] Figure 2 is a scanning electron microscope image of cement stone sample 1 without the composition at a working distance of 8.2 mm;

[0051] Figure 3 The figure is a scanning electron microscope image of the cement stone sample 2 containing the composition prepared in Example 4 at a working distance of 8.2 mm. DETAILED DESCRIPTION

[0052] The present invention will be further described below in conjunction with examples, but the examples of the present invention are only exemplary descriptions, and the implementation methods do not constitute limitations of the present invention under any circumstances.

[0053] Preparation of magnesium carbonate whiskers

[0054] Magnesium sulfate and potassium carbonate were purchased from Sinopharm Chemical Reagent Co., Ltd.

[0055] Prepare potassium carbonate solution:

[0056] Take 50g of potassium carbonate and mix it evenly with 50g of water to obtain a potassium carbonate aqueous solution with a potassium carbonate concentration of 50wt%.

[0057] The crystal length and crystal diameter of the magnesium carbonate whiskers prepared in Examples 1 to 3 were measured using a FBRM-600L focused beam reflectometer produced by Mettler Toledo, Switzerland.

[0058] Example 1

[0059] 1) Heat 100 g of water to 60° C., add 15 g of magnesium sulfate at a speed of 200 r / min while stirring to obtain a magnesium sulfate aqueous solution;

[0060] 2) at 60° C., first slowly dripping 35 g of a 50 wt % potassium carbonate aqueous solution into a magnesium sulfate aqueous solution (drip time is 50 min), then reacting for 6 h under stirring at 150 r / min, filtering the obtained reaction product, collecting the filter residue, and drying at 40° C. to obtain magnesium carbonate whiskers having a crystal length of 12 to 18 μm and a crystal diameter of 4 to 7 μm.

[0061] Example 2

[0062] 1) Heat 100 g of water to 70° C., add 13 g of magnesium sulfate at a speed of 250 r / min while stirring to obtain a magnesium sulfate aqueous solution;

[0063] 2) at 70° C., first slowly dropwise adding 30 g of a 50 wt % potassium carbonate aqueous solution into a magnesium sulfate aqueous solution (dropping time is 60 min), then reacting for 5 h under stirring at a speed of 100 r / min, filtering the obtained reaction product, collecting the filter residue, and drying at 45° C. to obtain magnesium carbonate whiskers having a crystal length of 12 to 18 μm and a crystal diameter of 4 to 7 μm.

[0064] Example 3

[0065] 1) Heat 100 g of water to 75° C., add 20 g of magnesium sulfate at a speed of 300 r / min while stirring to obtain a magnesium sulfate aqueous solution;

[0066] 2) at 75° C., first slowly drop 55 g of a 50 wt % potassium carbonate aqueous solution into a magnesium sulfate aqueous solution (dropping time is 70 min), then react for 8 h under stirring at 125 r / min, filter the obtained reaction product, collect the filter residue, and dry at 50° C. to obtain magnesium carbonate whiskers having a crystal length of 12 to 18 μm and a crystal diameter of 4 to 6 μm.

[0067] Preparation of composition

[0068] Nano-silicon dioxide: white solid powder, spherical particles, density between 2.60 and 2.70 g / cm 3 , particle size ranges from 5 to 23 nm, the median particle size is 10 nm, silicon dioxide content > 99%, purchased from Nanjing Tianxing New Materials Co., Ltd.;

[0069] Nano titanium dioxide: particle size of 5 to 7 nm, median particle size of 6 nm, purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.;

[0070] Sodium polyacrylate: industrial product, weight average molecular weight 2000, purchased from Shandong Wanhua Tianhe New Materials Co., Ltd.;

[0071] Polyacrylic acid: industrial product, weight average molecular weight 3000, purchased from Shandong Wanhua Tianhe New Materials Co., Ltd.;

[0072] Polyvinyl alcohol: industrial product, weight average molecular weight 1.2 million, purchased from Shanghai Houcheng Fine Chemical Co., Ltd.;

[0073] Polyvinyl pyrrolidone: industrial product, weight average molecular weight 1.2 million, purchased from Shanghai Houcheng Fine Chemical Co., Ltd.;

[0074] Carboxymethyl chitosan: industrial product, weight average molecular weight 550,000, purchased from Shandong Fengtai Biotechnology Co., Ltd.

[0075] Carboxymethyl cellulose: industrial product, weight average molecular weight 550,000, purchased from Shandong Fengtai Biotechnology Co., Ltd.

[0076] Hydroxypropyl chitosan: industrial product, weight average molecular weight 330,000, purchased from Shandong Fengtai Biotechnology Co., Ltd.

[0077] Example 4

[0078] 8.5 g of sodium polyacrylate with a weight average molecular weight of 2000 was added to 100 g of water, heated to 60° C., 25 g of nano silicon dioxide with a particle size of 5 to 23 nm and a median particle size of 10 nm was added while stirring at a speed of 800 r / min, and ultrasonic dispersion was performed for 5 min. 13 g of magnesium carbonate whiskers prepared in Example 1 and 0.92 g of polyvinyl pyrrolidone with a weight average molecular weight of 1.2 million were added in sequence under stirring at 60° C. and 500 r / min. Stirring was continued at 60° C. and 500 r / min for 50 min. The pH value was adjusted to 7.3 with magnesium sulfate and potassium carbonate, and the mixture was naturally cooled to room temperature to obtain a composition with a solid content of 32.17 wt %, which was a relatively viscous and stable suspension system.

[0079] Example 5

[0080] 8.5 g of polyacrylic acid with a weight average molecular weight of 3000 was added to 100 g of water, heated to 60° C., 25 g of nano titanium dioxide with a particle size of 5 to 7 nm and a median particle size of 6 nm was added while stirring at a speed of 800 r / min, and ultrasonic dispersion was performed for 5 min. Then, 14 g of magnesium carbonate whiskers prepared in Example 1 and 0.92 g of carboxymethyl cellulose with a weight average molecular weight of 550,000 were added in sequence under stirring at 60° C. and 500 r / min. Stirring was continued at 60° C. and 500 r / min for 50 min. The pH value was adjusted to 7.3 with magnesium sulfate and potassium carbonate, and the mixture was naturally cooled to room temperature to obtain a composition with a solid content of 32.62 wt%, which was a relatively viscous and stable suspension system.

[0081] Example 6

[0082] 5 g of sodium polyacrylate with a weight average molecular weight of 2000 was added to 100 g of water, heated to 70° C., 20 g of nano-silicon dioxide with a particle size of 5 to 23 nm and a median particle size of 10 nm was added while stirring at a speed of 1000 r / min, and ultrasonic dispersion was performed for 3 min. Then, 15 g of magnesium carbonate whiskers prepared in Example 2 and 0.82 g of polyvinyl alcohol with a molecular weight of 1.2 million were added in sequence under stirring at 70° C. and 300 r / min. Stirring was continued at 70° C. and 300 r / min for 30 min. The pH value was adjusted to 7 with magnesium sulfate and potassium carbonate, and the mixture was naturally cooled to room temperature to obtain a composition with a solid content of 31.42 wt%, which was a relatively viscous and stable suspension system.

[0083] Example 7

[0084] 11 g of sodium polyacrylate with a weight average molecular weight of 2000 was added to 100 g of water, heated to 75° C., 30 g of nano silicon dioxide with a particle size of 5 to 23 nm and a median particle size of 10 nm was added while stirring at a speed of 1200 r / min, and ultrasonic dispersion was performed for 7 min. Then, 13 g of magnesium carbonate whiskers prepared in Example 3 and 1.05 g of carboxymethyl chitosan with a weight average molecular weight of 550,000 were added in sequence under stirring at 75° C. and 400 r / min. Stirring was continued at 75° C. and 400 r / min for 60 min. The pH value was adjusted to 7.8 with magnesium sulfate and potassium carbonate, and the mixture was naturally cooled to room temperature to obtain a composition with a solid content of 35.50 wt %, which was a relatively viscous and stable suspension system.

[0085] Example 8

[0086] 11 g of polyacrylic acid with a weight average molecular weight of 3000 was added to 100 g of water, heated to 75° C., 30 g of nano titanium dioxide with a particle size of 5 to 7 nm and a median particle size of 6 nm was added while stirring at a speed of 1200 r / min, and ultrasonic dispersion was performed for 7 min. Then, 14 g of magnesium carbonate whiskers prepared in Example 3 and 1.05 g of hydroxypropyl chitosan with a weight average molecular weight of 330,000 were added in sequence under stirring at 75° C. and 400 r / min. Stirring was continued at 75° C. and 400 r / min for 60 min. The pH value was adjusted to 7.8 with magnesium sulfate and potassium carbonate, and the mixture was naturally cooled to room temperature to obtain a composition with a solid content of 35.92 wt%, which was a relatively viscous and stable suspension system.

[0087] Comparative Example 1

[0088] 100 g of water was heated to 60° C., and 25 g of nano-silicon dioxide with a particle size of 5 to 23 nm and a median particle size of 10 nm was added while stirring at a speed of 800 r / min. After ultrasonic dispersion treatment for 5 min, 13 g of the magnesium carbonate whisker prepared in Example 1 was added while stirring at 60° C. and 500 r / min. The mixture was continued to be stirred at 60° C. and 500 r / min for 50 min. The pH value was adjusted to 7.3 with magnesium sulfate and potassium carbonate, and the mixture was naturally cooled to room temperature to obtain a composition with a solid content of 27.53 wt%.

[0089] Comparative Example 2

[0090] To 100g of water, 8.5g of sodium polyacrylate with a weight average molecular weight of 2000 was added, the mixture was heated to 60°C, and stirred at a speed of 800r / min until the sodium polyacrylate was dissolved. After ultrasonic dispersion treatment for 5min, 0.92g of polyvinyl pyrrolidone with a weight average molecular weight of 1.2 million was added under stirring at 60°C and 500r / min. The mixture was continued to be stirred at 60°C and 500r / min for 50min. The pH value was adjusted to 7.3 with magnesium sulfate and potassium carbonate, and the mixture was naturally cooled to room temperature to obtain a composition with a solid content of 8.61wt%.

[0091] Experimental evaluation

[0092] G-grade oil well cement: purchased from Shandong Linqu Weisheng Special Cement Co., Ltd.;

[0093] Oil well cement fluid loss reducer QS-12S: a polymer fluid loss reducer purchased from Chengdu OMEC Petroleum Technology Co., Ltd.

[0094] Oil well cement drag reducer QS-20S: a sulfonated formaldehyde-acetone polycondensate drag reducer purchased from Chengdu OMEC Petroleum Technology Co., Ltd.;

[0095] Defoamer DF-B: a polyether-organosiloxane composite defoamer purchased from Chengdu OMEC Petroleum Technology Co., Ltd.

[0096] 1. Effect of composition on rheological properties of oil well cement

[0097] 1) Preparation of blank group cement slurry: Prepare cement slurry with a water-cement ratio of 0.44, mix 600g of G-grade oil well cement and 264g of tap water, and stir evenly at a speed of 12000r / min to obtain blank group cement slurry;

[0098] 2) preparing cement slurry of the experimental group: adding the composition to the cement slurry of the blank group in 1) so that the mass of the composition is 4%, 5%, or 6% of the mass of the G-grade oil well cement in the cement slurry of the blank group, and stirring at a speed of 12000 r / min to obtain cement slurry of the experimental group;

[0099] The compositions prepared in Examples 4 to 8, Comparative Example 1, and Comparative Example 2 were respectively used to prepare cement slurries of the experimental group according to step 2) of this experiment. The formulas of the cement slurries of the blank group and the experimental group are shown in Table 1;

[0100] Table 1. Cement slurry formula of blank group and experimental group

[0101]

[0102] 3) According to the standard SY / T 6544-2017 "Performance Requirements for Oil Well Cement Slurry", the apparent viscosity of the cement slurry in the blank group and the experimental group of this experiment at different rotation speeds was measured using a ZNN-D6 six-speed rotational viscometer (produced by Qingdao Haitongda Instrument Factory) at room temperature and normal pressure, and the fluidity index n and consistency coefficient K were calculated. The specific data are shown in Table 2.

[0103] Table 2. Rheological properties of cement paste in blank group and experimental group

[0104]

[0105] It can be seen from the data in Table 2 that in the experimental group cement slurry, when the addition amount of the composition prepared in Examples 4 to 8 is 4%, 5% and 6% of the mass of G-grade oil well cement, compared with the blank group, the fluidity index and consistency coefficient only change slightly, and the fluidity of the cement slurry in the experimental group after adding the composition is still very good, which shows that the composition has a weak effect on the fluidity index and consistency coefficient of G-grade oil well cement.

[0106] 2. Effect of composition on the thickening performance of oil well cement

[0107] 1) Preparation of blank group cement slurry: Prepare cement slurry with a water-cement ratio of 0.44, mix 600g of G-grade oil well cement and 264g of tap water, and stir evenly at a speed of 12000r / min to obtain blank group cement slurry;

[0108] 2) Preparation of experimental group cement slurry: Based on the blank group cement slurry in step 1) of this experiment, 30g of the composition was added so that the mass of the composition was 5% of the mass of the G-grade oil well cement in the blank group cement slurry, and the mixture was stirred at a speed of 12000r / min to obtain the experimental group cement slurry; the compositions prepared in Examples 4 to 8, Comparative Example 1 and Comparative Example 2 were respectively prepared according to step 2) to prepare the experimental group cement slurry;

[0109] 3) According to the standard SY / T 6544-2017 "Performance Requirements for Oil Well Cement Slurry", the initial consistency and thickening time of the cement slurry in the blank group and the experimental group of this experiment were measured at 60°C and normal pressure using a normal pressure thickener to evaluate the effect of the composition on the initial consistency and thickening time of the rheological properties of oil well cement. The specific consistency change curve is shown in Figure 1 .

[0110] analyze Figure 1 It can be seen that the initial consistency of the cement slurry in the experimental group is slightly lower than that of the cement slurry in the blank group without adding the composition. During the entire thickening process, the consistency change and the thickening curve are normal, which proves that the compositions prepared in Examples 4 to 8 have no adverse effects on the thickening time and performance of the cement slurry.

[0111] 3. Evaluation of compatibility between the composition and the drag reducer

[0112] 1) Preparing cement slurry containing the drag reducer and the composition: adding the drag reducer QS-20S to the cement slurry of the experimental group prepared in Experiment 2, so that the added amount of the drag reducer QS-20S is 0.1%, 0.2%, and 0.3% of the mass of the G-grade oil well cement, to obtain cement slurry containing the drag reducer and the composition;

[0113] 2) preparing cement slurry containing the composition: the same as the cement slurry of the experimental group in Example 2;

[0114] The compositions prepared in Examples 4 to 8, Comparative Example 1, and Comparative Example 2 are respectively prepared according to step 1) and step 2) to prepare cement slurry containing a drag reducer and the composition, and cement slurry containing the composition. The specific formula is shown in Table 3;

[0115] 3) According to the standard SY / T 6544-2017 "Performance Requirements for Oil Well Cement Slurries", the apparent viscosity of the cement slurry containing the drag reducer and the composition and the cement slurry containing the composition at different rotation speeds was measured using a ZNN-D6 six-speed rotational viscometer (produced by Qingdao Haitongda Instrument Factory) at room temperature and normal pressure, and the fluidity index n and consistency coefficient K were calculated. The specific data are shown in Table 4.

[0116] Table 3. Cement slurry containing drag reducer and composition, and cement slurry formula containing composition

[0117]

[0118] Table 4. Rheological properties of cement slurry containing drag reducer and composition, and cement slurry containing composition

[0119]

[0120] Analysis of the data in Table 4 shows that the compositions prepared in Examples 4 to 8 have good compatibility with the drag reducer QS-20S. As the amount of drag reducer QS-20S added increases, the fluidity of the cement slurry can be immediately improved, the fluidity index continues to increase, and the consistency coefficient continues to decrease.

[0121] 4. Evaluation of compatibility between the composition and the fluid loss reducer

[0122] 1) preparing cement slurry containing fluid loss reducer and drag reducer: preparing cement slurry with a water-cement ratio of 0.44, mixing 600g of G-grade oil well cement, 264g of tap water and 3g of defoamer DF-B, and then adding 9g of fluid loss reducer QS-12S and 3g of drag reducer QS-20S, so that the amount of fluid loss reducer QS-20S added is 1.5% of the mass of G-grade oil well cement, and the amount of drag reducer QS-20S added is 0.5% of the mass of G-grade oil well cement, and stirring at a speed of 12000r / min to obtain cement slurry containing fluid loss reducer and drag reducer;

[0123] 2) preparing cement slurry containing fluid loss additive, drag reducer and the composition: adding the composition to the cement slurry containing fluid loss additive and drag reducer prepared in step 1) of this experiment, stirring evenly at a speed of 12000r / min, so that the added amount of the composition is 4%, 5% and 6% of the mass of G-grade oil well cement, to obtain cement slurry containing fluid loss additive, drag reducer and the composition;

[0124] The compositions prepared in Examples 4 to 8, Comparative Example 1 and Comparative Example 2 were respectively used to prepare cement slurries containing fluid loss additive, drag reducer and the composition according to step 2) of this experiment. The specific formulas of cement slurries of each group in this experiment are shown in Table 5;

[0125] Table 5. Cement slurry containing fluid loss additive and drag reducer, cement slurry formula containing fluid loss additive, drag reducer and combination

[0126]

[0127] 3) According to the standard SY / T 6544-2017 "Performance Requirements for Oil Well Cement Slurries", a high-pressure fluid loss meter was used to measure the API water loss of cement slurries containing fluid loss reducers and drag reducers, and cement slurries containing fluid loss reducers, drag reducers and their combination at 60°C and 6.9 MPa. The specific data are shown in Table 6.

[0128] Table 6. API water loss of cement slurry containing fluid loss additive and drag reducer, and cement slurry containing fluid loss additive and drag reducer and combination thereof

[0129]

[0130] It can be seen from the data in Table 6 that adding the composition provided by the present invention to oil well cement will not affect the filtration control performance of the fluid loss reducer, and the compositions prepared in Examples 4 to 8 have good compatibility with the fluid loss reducer; in addition, since the composition contains nano-silicon dioxide particles and micron-sized magnesium carbonate whiskers, it also helps to control water loss to a certain extent, reducing the amount of water loss. Compared with the cement slurry containing only the fluid loss reducer and the drag reducer, the filtration loss reduction rate of the cement slurry prepared by the compositions of Examples 4 to 8 with 4%, 5%, and 6% of the mass of G-grade oil well cement added thereto is 5.13% to 10.26%, 7.69% to 17.95%, and 12.82% to 25.64% respectively; among them, the filtration loss reduction rate of the cement slurry prepared by the composition of Example 4 with 4%, 5%, and 6% of the mass of G-grade oil well cement added thereto is 7.69% to 17.95%, and 12.82% to 25.64% respectively. %, 17.95%, 12.82%; and compared with the cement slurry containing only fluid loss reducer and drag reducer, the fluid loss reduction rate of the cement slurry prepared by the composition of comparative example 1, on the basis of which 4%, 5%, 6% of the mass of G-grade oil well cement was added, was 2.56%, 2.56%, 7.69% respectively; the fluid loss reduction rate of the cement slurry prepared by the composition of comparative example 2, on the basis of which 4%, 5%, 6% of the mass of G-grade oil well cement was added, was 0%, 2.56%, 5.13% respectively. The fluid loss control performance of the compositions prepared by Examples 4 to 8 is significantly better than that of the compositions prepared by Comparative Examples 1 and 2. In addition, from the perspective of formulation, compared with Example 4, the composition prepared in Comparative Example 1 lacks the carboxyl-containing low-molecular polymer and the hydroxyl-containing high-molecular polymer, and the composition prepared in Comparative Example 2 lacks the nano-oxide and the inorganic whisker. Combined with the above experimental data, it can be shown that the nano-oxide, the inorganic whisker and the carboxyl-containing low-molecular polymer and the hydroxyl-containing high-molecular polymer in the composition have a synergistic effect in terms of water loss control performance, and the lack of any one of the raw materials will affect the water loss control performance of the composition.

[0131] 5. Effect of composition on compressive strength and flexural strength of oil well cement

[0132] 1) Prepare a blank cement slurry to be cured: prepare cement slurry with a water-cement ratio of 0.44, mix 800 g of G-grade oil well cement and 352 g of tap water, and stir evenly at a speed of 12000 r / min to obtain a blank cement slurry;

[0133] 2) Preparation of cement slurry for the experimental group to be cured: on the basis of the cement slurry for the blank group in step 1) of this experiment, the composition was added so that the mass of the composition was 4%, 4.5%, 5%, 5.5%, and 6% of the mass of the G-grade oil well cement in the cement slurry for the blank group, and the mixture was stirred evenly at a speed of 12000 r / min to obtain cement slurry for the experimental group; the compositions prepared in Examples 4 to 8, Comparative Example 1, and Comparative Example 2 were respectively prepared according to step 2) of this experiment to prepare cement slurry for the experimental group. The formulas of the cement slurries for the blank group and the experimental group are shown in Table 7;

[0134] Table 7. Cement slurry formulas for the blank group and experimental group to be cured

[0135]

[0136] 3) According to the standard SY / T 6544-2017 “Performance Requirements for Oil Well Cement Slurry”, the compressive strength and flexural strength of the cement paste formed by the blank group cement slurry and the experimental group cement slurry after curing for 7 days at different temperatures were measured, as shown in Tables 8 and 9.

[0137] Table 8. Compressive strength of cement paste formed after solidification of cement paste in the blank group and the experimental group after curing for 7 days at different temperatures

[0138]

[0139]

[0140] It can be seen from the data in Table 8 that after adding the composition prepared in any one of Examples 4 to 8 to oil well cement, the compressive strength of the cement paste is significantly improved. The average growth rates of the compressive strength of the cement stone with the composition added in Examples 4 to 8 of 4%, 4.5%, 5%, 5.5% and 6% of the G-grade oil well cement after curing at 30°C for 7 days compared with the blank group cement stone under the same curing conditions were 20%, 31.43%, 43.81%, 51.43% and 40.95% respectively; the average growth rates of the compressive strength of the cement stone with the composition added in Examples 4 to 8 after curing at 30°C for 7 days compared with the blank group cement stone under the same curing conditions were 33.49%, 41.40%, 47.44%, 46.96% and 42.79% respectively; the average growth rates of the compressive strength of the cement stone with the composition added in Examples 4 to 8 after curing at 90°C for 7 days compared with the blank group cement stone under the same curing conditions were 38.22%, 40.89%, 43.11%, 42.22% and 36.44% respectively. It can be seen that the compressive strength of the cement stone is significantly improved after the composition is added to the G-grade oil well cement. Among them, the composition prepared in Example 4 is added in an amount of 4%, 4.5%, 5%, 5.5%, and 6% of the G-grade oil well cement. The growth rates of the compressive strength of the cement stone after curing at 30°C for 7 days compared with the blank group cement stone under the same curing conditions are 23.81%, 38.10%, 52.38%, 61.90%, and 42.86%, respectively; the growth rates of the compressive strength after curing at 60°C for 7 days compared with the blank group cement stone under the same curing conditions are 37.21%, 51.16%, 60.47%, 60.47%, and 58.14%, respectively; the growth rates of the compressive strength after curing at 90°C for 7 days compared with the blank group cement stone under the same curing conditions are 44.44%, 51.11%, 51.11%, 53.33%, and 48.89%, respectively.The compressive strength of the cement stone with the composition prepared in Comparative Example 1 added in an amount of 4%, 4.5%, 5%, 5.5% and 6% of the G-grade oil well cement after curing at 30°C for 7 days, as compared with the blank group cement stone under the same curing conditions, increased by 9.52%, 9.52%, 14.29%, 23.81% and 19.05% respectively; the compressive strength of the cement stone with the composition added in Comparative Example 1 after curing at 60°C for 7 days, as compared with the blank group cement stone under the same curing conditions, increased by 9.30%, 11.63%, 13.95%, 23.26% and 18.60% respectively; the compressive strength of the cement stone with the composition added in Comparative Example 1 after curing at 90°C for 7 days, as compared with the blank group cement stone under the same curing conditions, increased by 17.78%, 22.22%, 20.00%, 22.22% and 17.78% respectively. %; the composition prepared in comparative example 2 with an addition amount of 4%, 4.5%, 5%, 5.5% and 6% of the G-grade oil well cement has a compressive strength growth rate of 4.76%, 9.52%, 19.05%, 19.05% and 14.29% respectively compared with the blank group cement stone under the same curing conditions after curing at 30°C for 7 days; the compressive strength growth rate after curing at 60°C for 7 days compared with the blank group cement stone under the same curing conditions is 6.98%, 9.30%, 13.95%, 16.28% and 11.63% respectively; the compressive strength growth rate after curing at 90°C for 7 days compared with the blank group cement stone under the same curing conditions is 13.33%, 17.78%, 22.22%, 22.22% and 4.44% respectively. By comparing the above data, it can be seen that the compositions prepared in Comparative Examples 1 and 2 have significantly lower ability to improve the compressive strength of cement paste than the compositions prepared in Examples 4 to 8. From the perspective of the formula, compared with Example 4, the composition prepared in Comparative Example 1 lacks the carboxyl-containing low-molecular polymer and the hydroxyl-containing high-molecular polymer, and the composition prepared in Comparative Example 2 lacks the nano-oxide and inorganic whiskers. Combined with the above experimental data, it can be shown that the nano-oxide, inorganic whiskers, carboxyl-containing low-molecular polymer, and hydroxyl-containing high-molecular polymer in the composition have a synergistic effect in improving the compressive strength of cement paste, and the lack of any one of the raw materials will affect the effect of the composition on improving the compressive strength of cement paste.

[0141] Table 9. Flexural strength of cement paste formed after solidification of cement paste in the blank group and the experimental group after curing for 7 days at different temperatures

[0142]

[0143]

[0144] It can be seen from the data in Table 9 that after adding the composition prepared in any one of Examples 4 to 8 to oil well cement, the flexural strength of the cement paste is significantly improved. The average growth rates of the flexural strength of the cement stone with the composition added in Examples 4 to 8 of 4%, 4.5%, 5%, 5.5%, and 6% of the G-grade oil well cement after curing at 30°C for 7 days compared with the blank group cement stone under the same curing conditions were 13.21%, 18.87%, 29.43%, 36.60%, and 31.70% respectively; the average growth rates of the flexural strength of the cement stone with the composition added in Examples 4 to 8 after curing at 30°C for 7 days compared with the blank group cement stone under the same curing conditions were 13.11%, 28.89%, 36.00%, 38.67%, and 28.89% respectively; the average growth rates of the flexural strength of the cement stone with the composition added in Examples 4 to 8 after curing at 90°C for 7 days compared with the blank group cement stone under the same curing conditions were 20.66%, 36.48%, 40.22%, 43.74%, and 30.99% respectively. It can be seen that the flexural strength of the cement stone is significantly improved after the composition is added to the G-grade oil well cement. Among them, the composition prepared in Example 4 is added in an amount of 4%, 4.5%, 5%, 5.5%, and 6% of the G-grade oil well cement. The growth rates of the flexural strength of the cement stone after curing at 30°C for 7 days compared with the blank group cement stone under the same curing conditions are 16.98%, 24.53%, 47.17%, 50.94%, and 49.06%, respectively; the growth rates of the flexural strength after curing at 60°C for 7 days compared with the blank group cement stone under the same curing conditions are 16.67%, 40%, 52.22%, 51.11%, and 42.22%, respectively; the growth rates of the flexural strength after curing at 90°C for 7 days compared with the blank group cement stone under the same curing conditions are 23.08%, 50.55%, 53.85%, 51.65%, and 37.36%, respectively.The growth rates of the flexural strength of the cement stone with the composition prepared in Comparative Example 1 of 4%, 4.5%, 5%, 5.5% and 6% of the G-grade oil well cement after curing at 30°C for 7 days compared with the blank group of cement stone under the same curing conditions are 7.55%, 9.43%, 13.21%, 16.98% and 13.21% respectively; the growth rates of the flexural strength of the cement stone with the composition prepared in Comparative Example 1 of 4%, 4.5%, 5%, 5.5% and 6% of the G-grade oil well cement after curing at 30°C for 7 days compared with the blank group of cement stone under the same curing conditions are 8.89%, 10.00%, 10.00%, 13.33% and 7.78% respectively; the growth rates of the flexural strength of the cement stone with the composition prepared in Comparative Example 1 of 90°C for 7 days compared with the blank group of cement stone under the same curing conditions are 10.99%, 13.19%, 14.29%, 13.19% and 7.78% respectively. 69%; the composition prepared in comparative example 2 with an addition amount of 4%, 4.5%, 5%, 5.5% and 6% of the G-grade oil well cement has a flexural strength growth rate of 3.77%, 7.55%, 13.21%, 11.32% and 9.43% respectively after curing at 30°C for 7 days compared with the blank group cement stone under the same curing conditions; the compressive strength growth rate after curing at 60°C for 7 days compared with the blank group cement stone under the same curing conditions is 3.33%, 6.67%, 8.89%, 10.00% and 6.67% respectively; the flexural strength growth rate after curing at 90°C for 7 days compared with the blank group cement stone under the same curing conditions is 3.30%, 8.79%, 9.89%, 10.99% and 6.59% respectively. By comparing the above data, it can be seen that the compositions prepared in Comparative Examples 1 and 2 have significantly lower ability to improve the flexural strength of cement stone than the compositions prepared in Examples 4 to 8. From the perspective of the formula, compared with Example 4, the composition prepared in Comparative Example 1 lacks the carboxyl-containing low-molecular polymer and the hydroxyl-containing high-molecular polymer, and the composition prepared in Comparative Example 2 lacks the nano-oxide and inorganic whiskers. Combined with the above experimental data, it can be shown that the nano-oxide, inorganic whiskers, carboxyl-containing low-molecular polymer, and hydroxyl-containing high-molecular polymer in the composition have a synergistic effect in improving the flexural strength of cement stone, and the lack of any one of the raw materials will affect the effect of the composition on improving the flexural strength of cement stone.

[0145] 6. Effect of composition on the microstructure of cement paste

[0146] The microscopic morphology of cement paste containing the compositions prepared in Examples 4 to 8 was observed using a Hitachi S4800 field emission scanning electron microscope. Here, the cement paste containing the composition prepared in Example 4 was taken as an example. The specific steps are as follows:

[0147] 1) Take equal amounts of the blank cement slurry in Experiment 5 and the cement slurry containing the composition prepared in Example 4 (wherein the amount of the composition added is 5% of the mass of the G-grade oil well cement) and cure them at 60° C. and normal pressure for 7 days to obtain cement paste sample 1 and cement paste sample 2;

[0148] 2) Two cement stone samples were respectively glued to a copper sample holder with conductive glue, vacuum-plated with gold, and their microstructures were observed and analyzed using a Hitachi S4800 field emission scanning electron microscope at an accelerating voltage of 5.5 kV and a working distance of 8.2 mm. Figure 2 , Figure 3 .

[0149] Figure 2 is a scanning electron microscope image of cement stone sample 1 without the composition at a working distance of 8.2 mm; Figure 3 This is a scanning electron microscope image of cement stone sample 2 containing the composition prepared in Example 4 at a working distance of 8.2 mm. Figure 2 and Figure 3 It can be seen that the surface of cement stone sample 2 has a lot more thin and long strips of substances than the surface of cement stone sample 1, which are inorganic whiskers added to the composition. It can also be seen that cement stone sample 2 has a denser microstructure than cement stone sample 1.

[0150] In Experiment 5, after the cement paste containing the compositions prepared in Examples 5 to 8 was cured at 60°C for 7 days under normal pressure, the same as in step 2) was observed. Figure 3 It can be seen that after the composition is added to the G-grade oil well cement, the size, morphology and stacking state of the hydration product of the G-grade oil well cement are effectively changed through the effects of hydration regulation, crystallization control, nanofilling, etc., so that it has a dense structure and achieves excellent mechanical properties.

[0151] Although the present invention has been described with reference to specific embodiments, it will be appreciated by those skilled in the art that various changes may be made without departing from the true spirit and scope of the present invention. In addition, the subject matter, spirit and scope of the present invention may be varied to accommodate specific situations, materials, material combinations and methods. All of these changes are included within the scope of the claims of the present invention.

Claims

1. A composition comprising nano oxide, inorganic whisker, carboxyl-containing low molecular polymer, hydroxyl-containing high molecular polymer and solvent.

2. The composition according to claim 1, characterized in that The composition comprises 20 to 30 parts by mass of the nano oxide, 13 to 21 parts by mass of the inorganic whisker, 5 to 11 parts by mass of the carboxyl-containing low molecular polymer, 0.82 to 1.05 parts by mass of the hydroxyl-containing high molecular polymer and 100 parts by mass of the solvent.

3. The composition according to claim 1 or 2, characterized in that The nano oxide is nano silicon dioxide and / or nano titanium dioxide; and / or The inorganic whiskers are magnesium carbonate whiskers; and / or The solvent is water.

4. The composition according to any one of claims 1 to 3, characterized in that The carboxyl-containing low molecular polymer is polycarboxylic acid and / or polycarboxylate; Preferably, the carboxyl-containing low molecular weight polymer is polyacrylic acid and / or sodium polyacrylate.

5. The composition according to any one of claims 1 to 4, characterized in that The hydroxyl-containing high molecular polymer is at least one of polyvinyl alcohol, polyvinyl pyrrolidone, carboxymethyl cellulose, carboxymethyl chitosan and hydroxypropyl chitosan.

6. The composition according to any one of claims 1 to 5, characterized in that The particle size of the nano oxide is 3nm to 35nm; and / or the median particle size is 5nm to 15nm; and / or The inorganic whisker has a length of 12 μm to 18 μm; and / or a diameter of 4 μm to 7 μm; and / or The weight average molecular weight of the carboxyl-containing low molecular polymer is 1500 to 3000; and / or The weight average molecular weight of the hydroxyl-containing high molecular polymer is 330,000 to 1.2 million.

7. A method for preparing a composition as claimed in any one of claims 1 to 6, comprising the following steps: 1) mixing the solvent, the carboxyl-containing low molecular polymer and the nano oxide to obtain a dispersion; 2) mixing the inorganic whisker, the hydroxyl-containing high molecular polymer and the dispersion, and adjusting the pH to obtain the composition.

8. The method according to claim 7, characterized in that In step 1), the solvent, the carboxyl-containing low molecular polymer and the nano-oxide are mixed under the condition of ultrasonic treatment at 60° C. to 75° C. for 3 min to 7 min.

9. The method according to claim 7 or 8, characterized in that: In step 2), the temperature of mixing the inorganic whiskers, the hydroxyl-containing high molecular polymer and the dispersion is 60° C. to 75° C.; and / or the pH is adjusted to 7 to 7.

8.

10. Use of the composition according to any one of claims 1 to 6 or the composition prepared by the method according to any one of claims 7 to 9 in oil and gas production, especially as an oil well cement enhancer.